ANALISIS PERSEPSI PELAJAR SEKOLAH MENENGAH ATAS TERHADAP PERKEMBANGAN TEKNOLOGI ARTIFICIAL INTELLIGENCE (AI) DALAM PEMBELAJARAN BAHASA - Hermawan, Dimas (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Education is a field that often undergoes transformation in line with developments over time, technology and societal demands. One of the latest breakthroughs that is in the spotlight in the education sector is the use of Artificial Intelligence (AI). This research aims to analyze high school students"™ perceptions of the development of Artificial Intelligence (AI) technology in language learning. This research uses a qualitative approach with questionnaire data collection techniques using google form instruments which are carried out online. Based on the research results, overall it can be concluded that high school students have a predominantly positive and open perception of the development of AI technology in language learning. However, there are also negative impacts from the use and utilization of AI technology in language learning, for this reason there needs to be a wise and responsible attitude in its use and utilization. Furthermore, it is hoped that the results of this research will provide valuable knowledge and insights for actors in the world of education, in using and utilizing technology AI effectively and selectively.